PENGARUH KESADARAN WAJIB PAJAK, PENGETAHUAN WAJIB PAJAK, SANKSI PERPAJAKAN DAN KUALITAS PELAYANAN PAJAK TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KABUPATEN BANTUL - Berlian Amalia Ramadhani; Martinus Budiantara (JURNAL ILMIAH EDUNOMIKA, 2024)
The investigation at SAMSAT Bantul explores the impact of tax awareness, tax knowledge, tax penalties, and service quality on motor vehicle tax compliance. The collected information was analyzed using SPSS version 21, applying multiple linear regression methods. A questionnaire was implemented as a data collection instrument and involved 155 respondents as sample subjects. The study revealed that the compliance of motor vehicle taxpayers is significantly influenced by tax knowledge and tax penalties. On the other hand, no substantial effects were observed from tax awareness and service quality on the compliance levels investigated. Keywords : Tax awareness, tax knowledge, tax penalties, service quality profitability